Microstructure, hardness and superconducting properties of Ag added ErBa2Cu307-δ - Ahmad Kamal Yahya,; Faizah Md. Salleh, (Universiti Kebangsaan Malaysia, 2000)
The effect of Ag addition (0-25 wt. %) on the superconductivity, microstructure and hardness of ErBa2Cu307-δ (Erl23) was investigated. A sudden drop in the room temperature electrical resistivity was observed when Ag was added. For the 5 wt % Ag content, a significant increase in Tc zero (zero-resistance temperature) from 88 K (pure sample) to 91 K was observed. The increase in Tc was explained in terms of possible increase in oxygen content. However, Tc sifar remained approximately constant at 91 K for further addition of Ag (10, 15 and 20 wt. %). At 25 wt. % Ag, Tc zero drops drastically to 69 K. X-ray powder diffraction, Energy Dispersive X-ray Analysis (EDAX) and Scanning Electron Microscopy analysis indicate that Ag did not substitute in the Er123 lattice but instead resides between grain boundaries. Vickers Hardness measurements showed optimum hardness at 15 wt. % Ag content. The increase in hardness was due to the changes in the microstructure of the material.